KRITERIA PENDIDIK PERSPEKTIF BUYA HAMKA (Analisis Tafsir Al-Azhar dan Pemikirannya Tentang Pendidik) - Muhammad Hafizh; Sarah Dina; Sharikhul Hanif; Mudzakir Ali (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This research raises the issue of Hamka's thoughts regarding the criteria for educators in terms of his tafsir book. The book of exegesis written certainly contains tendencies and influences from the thoughts of the author. In this case the author wants to make relevance between his thoughts and his interpretation of Qs. YÅ«suf/12:4-6 in Tafsir Al-Azhar. This research is useful to know the various criteria of educators, their perspectives on the interpretation of Qs. YÅ«suf/12:4-6 and their relevance to their thoughts about educators. This research is based on literature studies and includes qualitative types (descriptive analysis that is useful for dismantling and finding educator criteria on Hamka's interpretation). The result of this study is in the form of seven criteria educators perspective Hamka in his interpretation of the verse has a relationship with his thoughts about educators.